A set-theoretic proof of the representation of MV-algebras by sheaves. Issue 4 (2nd October 2022) - Estrada, Alejandro; Poveda, Yuri A.
ABSTRACT: In this paper, we provide a set-theoretic proof of the general representation theorem for MV-algebras, which was developed by Dubuc and Poveda in 2010. The theorem states that every MV-algebra is isomorphic to the MV-algebra of all global sections of its prime spectrum. We avoid using topos theory and instead rely on basic concepts from MV-algebras, topology and set theory.